Does local government matter? : how urban policies shape civic engagement - Sharp, Elaine B. (Globalization and community, 2012)
Employing policy feedback theory to a series of local government programs, Elaine B. Sharp shows that these programs do have consequences with respect to citizens' political participation. With this clear-eyed analysis, Sharp finds that local governments' social program activities actually dampen participation of the have-nots, while cities' development programs reinforce the political involvement of already-privileged business interests.